2015
DOI: 10.18632/oncotarget.6782
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus pulposus phenotypic markers to determine stem cell differentiation: fact or fiction?

Abstract: Progress in mesenchymal stem cell (MSC) based therapies for nucleus pulposus (NP) regeneration are hampered by a lack of understanding and consensus of the normal NP cell phenotype. Despite the recent consensus paper on NP markers, there is still a need to further validate proposed markers. This study aimed to determine whether an NP phenotypic profile could be identified within a large population of mature NP samples.qRT-PCR was conducted to assess mRNA expression of 13 genes within human non-degenerate artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 53 publications
9
57
0
Order By: Relevance
“…Compared to conventional marker genes bT and bKRT19 were rather difficult to detect, exemplified by the large number of non-detectable samples in tissues with low expression. In agreement with other studies, we found that the NP/IVD can be distinguished from AC by high expression of bPax1 and bFoxf1 [7,13]. These genes exhibited the highest differential expression in our study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Compared to conventional marker genes bT and bKRT19 were rather difficult to detect, exemplified by the large number of non-detectable samples in tissues with low expression. In agreement with other studies, we found that the NP/IVD can be distinguished from AC by high expression of bPax1 and bFoxf1 [7,13]. These genes exhibited the highest differential expression in our study.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, NP specific marker genes are increasingly used as readout to develop stem cell differentiation protocols for NP regeneration [11,12]. However, a recent report described large variation for NP and AF marker genes in human cell isolates, which prevented separation of NP and AF tissue based on phenotypic markers [13]. Only PAX1 and FOXF1 were confirmed to distinguish NP tissue from AC and at the protein level NP from AC.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, the knockout of all WNT genes led to significantly decreased PAX1 and FOXF1 expression, markers suggested to be representative of the healthy, mature NP cell phenotype . Interestingly, the overexpression of WNT5A and WNT11 genes increased PAX1 expression by five‐ and ninefold, respectively, versus the GFP control at day 0 of redifferentiation; however, this effect was attenuated by day 28.…”
Section: Discussionsupporting
confidence: 64%
“…Several previous studies have investigated specific markers for NP cells [42-45]. In this study, high-magnitude (20% deformation) compression down-regulated the expression of these NP markers (keratin 19, glypican and CA XII) compared with low-magnitude (2% deformation) compression.…”
Section: Discussionmentioning
confidence: 66%